Saúde é democracia?: experiência da participação popular no município de Ipatinga - Elizabeth da Costa Batista (2005)
Since the SUS implementation, in the 90s, it has been possible to observe the change from a political, administrative, and financially centered system to a scene where thousands of agents started to constitute fundamental citizens in the field of health. The objective of this work is to understand how these different actors have absorbed and guaranteed the community the right to participate in the decision ofhealth public politics. This research tries also to investigate the democratic speech and the participative practice implemented by the Workers Party (PT) in the city of Ipatinga, during the period of 1989 and 2004. This work uses as theoretical referential the Communicative Action Theory of Habermas and, from this theory, a model of democracy which is understood as the institutionalization of the discursive processes of opinion and will formation, in a way that the political decisions aredefined in a participative form, from the association between the representative mechanisms and the public debate propitiating, therefore, a process of reflection, discussion, and negotiation between the social actors involved, proper of the linguistic agreement, which guarantees the respect and the consideration of the citizens common aspirations and collective interests. The results obtained indicate that there is an important democratic history in the City, but with indications, however,of retrocessions in the participative practices of the health sector, as the reproduction of traditional practices of government is verified.